The application of treated mangrove tannins as a mud thinner agent [electronic resource] - 369156 Nor Hidayah Mohd. Sarayany (2006)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2006